Scaling up impact on nutrition: What will it take? - Gillespie, Stuart; Menon, Purnima; Kennedy, Andrew (Elsevier, 2015)
Despite consensus on actions to improve nutrition globally, less is known about how to operationalize the right mix of actions—nutrition-specific and nutrition-sensitive—equitably, at scale, in different contexts. This review draws on a large scaling-up literature search and 4 case studies of large-scale nutrition programs with proven impact to synthesize critical elements for impact at scale. Nine elements emerged as central: 1) having a clear vision or goal for impact; 2) intervention characteristics; 3) an enabling organizational context for scaling up; 4) establishing drivers such as catalysts, champions, systemwide ownership, and incentives; 5) choosing contextually relevant strategies and pathways for scaling up, 6) building operational and strategic capacities; 7) ensuring adequacy, stability, and flexibility of financing; 8) ensuring adequate governance structures and systems; and 9) embedding mechanisms for monitoring, learning, and accountability. Translating current political commitment to large-scale impact on nutrition will require robust attention to these elements.